2019
DOI: 10.3390/cancers11121910
|View full text |Cite
|
Sign up to set email alerts
|

Spatial EGFR Dynamics and Metastatic Phenotypes Modulated by Upregulated EphB2 and Src Pathways in Advanced Prostate Cancer

Abstract: Advanced prostate cancer is a very heterogeneous disease reflecting in diverse regulations of oncogenic signaling pathways. Aberrant spatial dynamics of epidermal growth factor receptor (EGFR) promote their dimerization and clustering, leading to constitutive activation in oncogenesis. The EphB2 and Src signaling pathways are associated with the reorganization of the cytoskeleton leading to malignancy, but their roles in regulating EGFR dynamics and activation are scarcely reported. Using single-particle track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 89 publications
(117 reference statements)
2
15
0
Order By: Relevance
“…As seen on Figure 1 , functional studies have revealed many kinases to be involved in prostate cancer biology. Growth factor and cytokine signaling conveyed by different receptor kinases (e.g., ErbB2 [ 47 ], FGFRs [ 48 , 49 , 50 , 51 , 52 , 53 ], IGF1R [ 54 , 55 , 56 , 57 , 58 ], CXCRs [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]) as well as plasma membrane and cytoplasm located kinases are shown to critically influence prostate cancer. As an example, MAPKs are serine/threonine kinases that link extracellular signals to downstream machinery that influences cell behaviors.…”
Section: Post-translational Modifications In Prostate Cancermentioning
confidence: 99%
“…As seen on Figure 1 , functional studies have revealed many kinases to be involved in prostate cancer biology. Growth factor and cytokine signaling conveyed by different receptor kinases (e.g., ErbB2 [ 47 ], FGFRs [ 48 , 49 , 50 , 51 , 52 , 53 ], IGF1R [ 54 , 55 , 56 , 57 , 58 ], CXCRs [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]) as well as plasma membrane and cytoplasm located kinases are shown to critically influence prostate cancer. As an example, MAPKs are serine/threonine kinases that link extracellular signals to downstream machinery that influences cell behaviors.…”
Section: Post-translational Modifications In Prostate Cancermentioning
confidence: 99%
“…more mesenchymal) that the CTCs; moreover, it can have variable cell fractions too (Figure 5C, right). Moreover, three other CTC datasets from prostate, myeloma, and breast cancer [44][45][46] are mapped onto distinct model contour lines (Figure S7A). Interestingly, measuring both tumor and CTC MLR score allows to identify a single (k, c) parameter combination.…”
Section: Exploring the Predictive Power Of Several Measurements That Quantify Tumor Aggressivenessmentioning
confidence: 99%
“…Although, EGF functions as the predominant ligand for EGFR in early phases of localized prostate cancer formation but during late phase of metastatic CRPC development, TGFA plays a characteristic leading role in EGFR activation [98]. EGFR is primarily responsible for constitutive activation of oncogenesis through subsequent stimulation of diverse essential signaling mediators in order to trigger self-sufficiency in growth signaling through enhancement of prostate cancer cell growth and proliferation programs [99]. EGFR plays the most critical modulatory role during the development of androgen independence through post translational modification of androgen receptor (AR) in order to reactivate its downstream signaling in castration resistant condition [100].…”
Section: Role Of Major Oncogenes In Castration Resistant (Crpc) Prostate Cancer Advancementmentioning
confidence: 99%
“…Several pre-clinical studies on mouse model and clinical trials have indicated limited efficacies of EGFR targeting therapeutic inhibitors like Gefitinib, Erlotinib and BIBW-2992 due to overproduction of EGFR ligands by prostate tumor and its stromal microenvironments [101]. Currently, a number of EGFR targeting combination therapy and immunotherapy based approaches are evaluating their efficiencies for treatment of hormone refractory prostate cancer [97][98][99][100][101].…”
Section: Role Of Major Oncogenes In Castration Resistant (Crpc) Prostate Cancer Advancementmentioning
confidence: 99%